The synthesis of novel Pt-based nanoparticles - Leteba, Gerard (Centre for Materials Engineering, 2015)
The ultimate goal of this project was to explore alternative and various synthetic routes for the design and fabrication of V@Pt core-shell and bimetallic nanoparticles.